Comparative analysis of perceived stress in dermatologists and other physicians during national lock‐down and COVID‐19 pandemic with exploration of possible risk factors: A web‐based cross‐sectional study from Eastern India. Issue 4 (6th July 2020) - Podder, Indrashis; Agarwal, Komal; Datta, Subhendu
Abstract: Since the declaration of coronavirus disease 2019 (COVID‐19) as global pandemic, several countries including India have enforced a national lock‐down. We aimed to compare the perceived stress of dermatologists and nondermatologists, due to lock‐down and COVID‐19 pandemic and analyze the role of possible risk factors. We conducted a web‐based cross‐sectional study to determine the perceived stress of doctors using the Perceived Stress Scale‐10 and evaluate possible risk factors. Among 384 valid responders, we had 37.5% dermatologists and 62.5% nondermatologists. Perceived stress was more in nondermatologists compared to dermatologists, but not statistically significant ( P = 0.1). Degree of stress was also comparable ( P = 0.5). Higher stress was significantly associated with females and unmarried individuals in both groups. Risk of infecting self or colleagues or family members and lack of protective gear at work place were top causes of stress. Perceived stress is increased in all doctors due to COVID‐19 pandemic and lock‐down. Even dermatologists have developed high stress due to current situation, comparable to nondermatologists, despite being traditionally considered an outpatient speciality with minimum stress. Thus, proper mental health care policies should be adopted for all doctors, including dermatologists.